Pengaruh Keteladanan Guru dan Penggunaan Gadget Terhadap Kepribadian Peserta Didik - Khoiruddin Khoiruddin; Ahmad Thoyyib Mas’udi; Muhammad Najib (Pascasarjana Universitas Qomaruddin, 2025)
In the era of globalization, everything is easy just by using a gadget, from accessing various information, public viewing to social transactions. However, excessive and inappropriate use of gadgets will have an impact on students' personalities. The personality of students should be of special and important attention to become the main mainstream of education in Indonesia, both in the formal, non-formal and informal realms. There are several factors that influence children's character development, including the teacher's example and the use of gadgets. This research aims to determine the influence of teacher example and the use of gadgets on the personality of students at MTs Ihyaul Ulum Cangaan Ujungpangkah Gresik. This research is quantitative research using an associative or affiliate strategy. The population in this study were all MTs Ihyaul Ulum students consisting of 3 classes with a total of 99 students. The sample in this study will be determined using a simple random sampling technique by determining the number of samples using the Michael and Issac formula with an error rate of 5%. Internal resources of madrasa teachers and all MTs Ihyaul Ulum students were involved in this research. This research will be conducted at MTs Ihyaul Ulum Cangaan Ujungpangkah Gresik. The instrument that will be used in this research is an online questionnaire or closed questionnaire via Google Form. The questionnaire will be prepared based on a Likert scale. Technical data analysis will be carried out using hypothesis testing, t test, and F test.